Assessment Strategies in Reading Class through Blended Learning - Saefurrohman, Saefurrohman; Susiloningtyas, Riyanti (Proceedings Series on Physical & Formal Sciences, 2022)
This research aimed at investigating strategies of reading assessment used by English vocational teachers in Banyumas. Thirty-five English Vocational High school teachers were selected as respondents of this research. Data collection techniques of this research were questionnaire, the interview Quantitative data were analyzed by scoring the result and making a percentage. And qualitative data from interviews and documents were analyzed by data reduction and data display. The results show that most EFL teachers in Banyumas, Indonesia, used an approach to reading assessment that included students developing their own ideas or providing comments. Another strategy is checking students’ capacity to read and measure the whole of the content presented to them that prompts them to write or speak. The next straegy is checking the student’s comprehension using Four Corners games.